Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Threshold photoelectron spectroscopy and dissociative photoionization of benzonitrile - Kamer, Jerry; Schleier, Domenik; Donker, Merel; Hemberger, Patrick; Bodi, Andras; Bouwman, Jordy (Physical Chemistry Chemical Physics)
The seven parallel dissociative ionization channels of benzonitrile yield highly stable fragment ions with commensurate abundance, underlining the potential role of the benzonitrile cation as hub species in the interstellar medium.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Threshold photoelectron spectroscopy of trimethylborane and its pyrolysis products - Schleier, Domenik; Gerlach, Marius; Schaffner, Dorothee; Mukhopadhyay, Deb Pratim; Hemberger, Patrick; Fischer, Ingo (Physical Chemistry Chemical Physics)
A new decomposition mechanism for trimethylborane at high temperatures has been discovered.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Measurement and modelling solubility of amino acids and peptides in aqueous 2-propanol solutions - Do, Hoang Tam; Franke, Patrick; Volpert, Sophia; Klinksiek, Marcel; Thome, Max; Held, Christoph (Physical Chemistry Chemical Physics)
In this work the solubility of 15 amino acids and 18 peptides in aqueous 2-propanol solutions was successfully modelled using PC-SAFT that used recently determined experimental melting properties as input data.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Thermostable water reservoirs in the interlayer space of a sodium hectorite clay through the intercalation of γ-aminopropyl(dimethyl)ethoxysilane in toluene - Keil, Waldemar; Zhao, Kai; Oswald, Arthur; Bremser, Wolfgang; Schmidt, Claudia; Hintze-Bruening, Horst (Physical Chemistry Chemical Physics)
Thermostable compartmentalized sodium-water sites through intercalated γ-aminopropyl-dimethyl-ethoxy silane in synthetic hectorite.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Diffusion of the carbon dioxide–ethanol mixture in the extended critical region - Chatwell, René Spencer; Guevara-Carrion, Gabriela; Gaponenko, Yuri; Shevtsova, Valentina; Vrabec, Jadran (Physical Chemistry Chemical Physics)
The effect of traces of ethanol in supercritical carbon dioxide on the mixture's thermodynamic properties is studied by molecular simulations and Taylor dispersion measurements.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Recombination mechanisms of luminescence type gas sensors - Poeplau, Michael; Ester, Stephan; Henning, Bernd; Wagner, Thorsten (Physical Chemistry Chemical Physics)
The impact of the recombination mechanisms in luminescent materials is discussed with regard to luminescence based gas-sensing applications and the use of semiconducting materials, as an alternative to organic–metal complexes, is outlined.

In silico investigation of Cu(In,Ga)Se2-based solar cells - Mirhosseini, Hossein; Kormath Madam Raghupathy, Ramya; Sahoo, Sudhir K.; Wiebeler, Hendrik; Chugh, Manjusha; Kühne, Thomas D. (Physical Chemistry Chemical Physics)
State-of-the-art methods in materials science such as artificial intelligence and data-driven techniques advance the investigation of photovoltaic materials.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Tumbling with a limp: local asymmetry in water's hydrogen bond network and its consequences - Elgabarty, Hossam; Kühne, Thomas (Physical Chemistry Chemical Physics)
Ab initio molecular dynamics simulations of ambient liquid water and energy decomposition analysis have recently shown that water molecules exhibit significant asymmetry between the strengths of the two donor and/or the two acceptor interactions.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Electron paramagnetic resonance study of ferroelectric phase transition and dynamic effects in a Mn2+ doped [NH4][Zn(HCOO)3] hybrid formate framework - Navickas, Marius; Giriūnas, Laisvydas; Kalendra, Vidmantas; Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero; Mączka, Mirosław; Pöppl, Andreas; Banys, Jūras; Šimėnas, Mantas (Physical Chemistry Chemical Physics)
EPR spectroscopy reveals the universality class and dynamic effects of the [NH4][Zn(HCOO)3] hybrid formate framework.